2015 IEEE International Conference on Cloud Engineering 2015
DOI: 10.1109/ic2e.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

EAGER: Deployment-Time API Governance for Modern PaaS Clouds

Abstract: Abstract-To track, control, and compel reuse of web APIs, we investigate a new approach to API governance -combined policy, implementation, and deployment control of web APIs. Our approach, called EAGER, provides a software architecture that integrates into PaaS platforms to support systemwide, deployment-time enforcement of governance policies. Specifically, EAGER checks for and prevents backward incompatible API changes from being deployed into production PaaS clouds, enforces service reuse, and facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The last group of literature in which no definition for API Management was found, consists of papers which focus on a domain that is closely related to API management or may be regarded to be within the scope of this topic. For example, in their work, Jayathilaka et al [29] investigate a new approach to API governance, which the authors of this SLR have identified to be a subtopic within the field of API management. Additionally, Jayathilka et al's paper contains practices and capabilities related to the API gateway and versioning.…”
Section: Defining Api Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…The last group of literature in which no definition for API Management was found, consists of papers which focus on a domain that is closely related to API management or may be regarded to be within the scope of this topic. For example, in their work, Jayathilaka et al [29] investigate a new approach to API governance, which the authors of this SLR have identified to be a subtopic within the field of API management. Additionally, Jayathilka et al's paper contains practices and capabilities related to the API gateway and versioning.…”
Section: Defining Api Managementmentioning
confidence: 99%
“…Therefore, security for APIs is of utmost importance to protect the underlying assets from unauthenticated and unauthorized access. [18] [ 18,21,25,29,34,35,40,48,50] Service Discovery…”
Section: Key and Certificate Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we have developed Cerebro for use with EA-GER (Enforced API Governance Engine for REST) [24] -an API governance system for PaaS clouds. EAGER attempts to enforce governance policies at the deploymenttime of cloud applications.…”
Section: Introductionmentioning
confidence: 99%